2004
DOI: 10.1023/b:mcbi.0000009871.04141.64
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular diffusion of adenosine phosphates is locally restricted in cardiac muscle

Abstract: Recent studies have revealed the structural and functional interactions between mitochondria, myofibrils and sarcoplasmic reticulum in cardiac cells. Direct channeling of adenosine phosphates between organelles identified in the experiments indicates that diffusion of adenosine phosphates is limited in cardiac cells due to very specific intracellular structural organization. However, the mode of diffusion restrictions and nature of the intracellular structures in creating the diffusion barriers is still unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 20 publications
7
70
0
Order By: Relevance
“…ATPases (28,30,39). The crystal-like arrangement seen in our study is consistent with this hypothesis and suggests the unitary structure of the studied muscle cells.…”
Section: C765supporting
confidence: 91%
See 1 more Smart Citation
“…ATPases (28,30,39). The crystal-like arrangement seen in our study is consistent with this hypothesis and suggests the unitary structure of the studied muscle cells.…”
Section: C765supporting
confidence: 91%
“…In addition, kinetic studies have shown a direct supply of endogenous ADP from ATPases to mitochondria (30,34). Such interaction can be explained by the existence of localized intracellular diffusion restrictions (28,39). A mild treatment of the fibers with trypsin leads to the removal of these diffusion restrictions, and at the same time, distribution of mitochondria in the fiber is changed from regular arrangement in the control to random distribution after the treatment (28).…”
mentioning
confidence: 99%
“…These results are in good agreement with earlier data (Veksler et al 1995;Kuznetsov et al 1996;Ventura-Clapier et al 1998;Saks et al 2004). Since the fibre diameter is usually bigger in fast glycolytic muscles, these data show very clearly the differences in the intracellular organization between different muscle types, and the very high apparent K m values are caused by specific local restrictions of the diffusion of ADP inside the type I oxidative fibres (Abraham et al 2002;Vendelin et al 2004).…”
supporting
confidence: 92%
“…CK, which catalyzes the reaction of ATP + creatine (Cr) to phosphocreatine (PCr), plays a role in this circuit in several ways. First, PCr has a greater diffusion rate than ATP (Vendelin et al, 2004). Second, Cr and PCr are metabolically inert in comparison to ADP and ATP, as no enzymes other than CK bind them, which means that PCr only gets depleted where CK is localized.…”
Section: Regulation Of Energy Metabolism Through the Phosphocreatine mentioning
confidence: 99%